Video-assisted thoracoscopy the total mesoesophageal excision and systematic en bloc mediastinal lymph node dissection - Kang, Mingqiang (J Vis Surg, 2016)
A 59-year-old female presented with upper esophageal squamous cell carcinoma had swallowing disorders. We performed the total mesoesophageal excision (TME) and systematic en bloc mediastinal lymph node dissection via VATS. The surgery process was successful and the postoperative course was uneventful. A squamous cell carcinoma of stage T1aN0M0 was identified on pathological examination, and the postoperative examination of esophageal swallow diatrizoate meglumine and computed tomography (CT) scan confirmed no anastomosis fistula and no signs of recurrence.